GASTROINTESTINAL PARASITES IN THREE SPECIES OF TELMATOBIUS (ANURA: TELMATOBIIDAE) IN THE HIGH ANDES, PERU - Chero, Jhon (2014)
During a parasitological study of semiaquatic amphibians from the high Andean region of Peru, 83 specimens of the genus Telmatobius [T. jelskii (n = 56), T. marmoratus (n = 17) and T. peruvianus (n = 10)] were purchased from markets in Lima, Peru where it is consumed liquefied Andean frogs purposes of traditional medicine, during the months of April 2009 to September 2013. According to their conservation status IUCN, T. peruvianus and T. marmoratus are vulnerable species (VU), while T. jelskii is near Threatened (NT). The parasitological analysis included total necropsy of each amphibian and search, collection, identification and standardization of its helminth fauna. The nematodes dominated in species richness and percentage of collected individuals (n = 6; 93.19%), followed by trematodes (n = 2; 4.94%), cestodes (n = 2, 1.46%) and finally, Acantocephala (n = 2; 0.42%). The three most important helminths found in Telmatobius were Hedruris moniezi, Aplectana hylambatis and Gorgoderina parvicava fluke. The parasite prevalence and abundance of all species of Telmatobius showed no association with the length of the host. Sex ratio of T. jelskii and prevalence of G. parvicava, H. moniezi, and H. moniezi were noted. Haematoloechus pukinensis, Ophiotaenia sp., H. moniezi, Cosmocercidae gen. sp., Falcaustra mascula, Aplectana vellardi, Oncicola sp. and Centrorhynchus sp. are new host records for T. jelskii. Ophiotaenia sp. is a new geographical record to the Peruvian helminthological fauna. Oncicola is reported for the first time in amphibians from Peru. Centrorhynchus sp. is reported for the second time in Peru. T. peruvianus represents a new host record for A. hylambatis and F. mascula.